The Effectiveness of Problem-Based Learning with Model Eliciting Activities Approach towards Problem Solving Competency - Candra Kusuma Nurjanah; Supandi Supandi; Agnita Siska Pramasdyahsari (International Journal of Research in Education, 2023)
The purpose of this study was to determine whether there was a difference in the average score and the effectiveness of problem based learning with the mathematics model eliciting activities approach to problem solving ability. The type of study is a quantitative research with a quasi experimental design using a pretest-posttest only control group design. The population in this study was class VIII SMPN 5 Jepara in the academic year 2022/2023 which consist of two classes. The sampling technique was carried out by purposive sampling technique, class VIII A was the control class and class VIII B was the experimental class. The data obtained through the pretest and posttest values were then processed by normality test, homogeneity test, T-Test, and N-Gain. The results obtained from the T-Test is a problem based learning model with an approach model of bringing up mathematical activities with a number of respondents 32 students and a mean of 81.22. While the control class taught by conventional learning has 31 students as respondents and the mean is 71.65. The value of t_count = 6.011 and a significance level of 5% obtained t_table = 1.999. Based on the t value, it can be written t_table (5% = 1.999) < t_count (6.011), then the results of the data analysis can be said that  is rejected and   is accepted so that "there is a difference in the average problem-solving ability of students in class that uses the learning problem learning model raises students' mathematical activities. The next test is the N-Gain test. It is found that the experimental class mathematical problem solving is better than the control class, namely the increase in the experimental class has a medium category that is 0.47 and the increase in the control class has a low category that is 0.21 so that it can be said to be increasing and effective.